Lighting as an Aspect of Cinematography in Transforming African Oral Traditions to Modern Media and its Psychological Effects using Kúnlé Afọláyan’s Aníkúlápó - Afolabi, Amos Adelekan; Ganiyu, Kareeem Kolawole; Olugbenga, Babatunde Covenant (BIRCU, 2025)
Lighting is a significant component of cinematography, which influences viewers' visual, psychological and emotional experiences. With an emphasis on Kúnlé Afọláyan's 2022 film Aníkúlápó, this paper explores the crucial role that lighting plays in converting African oral traditions into contemporary cinematic storytelling. Lighting becomes a crucial visual language that transmits ideas, emotions, and cultural subtleties that were previously expressed through speech, gestures, and surroundings when oral storytelling moves from traditional forms to the medium of cinema. Lighting in Aníkúlápó invokes the spiritual and moral aspects of African oral storytelling in addition to illuminating sights. While artificial lighting heightens the dramatic tension and highlights crucial moments of love, treachery, and divine intervention, the deliberate use of natural light highlights the film's ties to Yoruba cosmology and traditional locations. A psychological effect is produced by the way light and shadow interacts, engrossing viewers in the story and bringing them closer to the ancient world. This research investigates the many ways in which different lighting strategies captivate viewers. Lighting not only supports the visual narrative but also strengthens cultural memory and identity by emphasizing cultural symbols and enhancing emotional depth. Additionally, the psychological impacts of lighting are examined, with a focus on how it might emotionally engage viewers and help them develop a stronger bond with the stories. Afọláyan illustrates through Aníkúlápó how lighting unites contemporary cinematic expression with traditional African narrative, converting oral traditions into visually striking and culturally relevant media.